Study the Effect of Fuel Pressure on the Operating and Phases Parameters For PF400J Dense Plasma Focus Device - Majeed, R. H.; Jassim, M. K.; Hady, F. M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Theoretical calculations are achieved to study the effect of different deuterium pressures on various characteristics parameters for PF400J plasma focus using an international computer code. Axial and radial velocities, voltage tube, plasma temperatures, and neutron yields at different operating deuterium pressures are computed. Neutron emission has been calculated in the device. The maximum total neutron yield calculated is of the order of and neutrons per shot for entire pressure used. The computed results agree reasonably well with the published neutron yield curves.